Cytotoxic sesquiterpenoids from soft coral Capnella imbricata - Phan, Chin Soon; Takashi Kamada; Takahiro Ishii; Toshiyuki Hamada; Charles Santhanaraju Vairappan (2019)
A new sesquiterpene, capgermacrene H (1) was isolated together with 7 other compounds, capgermacrenes A-G (2-8), from a population of soft coral Capnella imbricata collected from Mantanani Island, Sabah, Malaysia. The structure of this metabolite was elucidated based on spectroscopic data such as nuclear magnetic resonance and high-resolution electrospray ionization mass spectrometry. Capgermacrene A (2) showed potent cytotoxicity against adult T-cell leukemia, S1T cells at half-maximal inhibitory concentration of 0.79 µg/mL.